Magnitude of Blood Pressure Change After Endovascular Therapy and Outcomes: Insight From the BP-TARGET Trial. Issue 3 (March 2022) - Anadani, Mohammad; Maïer, Benjamin; Escalard, Simon; Labreuche, Julien; de Havenon, Adam; Sabben, Candice; Lapergue, Bertrand; Gory, Benjamin; Richard, Sebastien; Sibon, Igor; Desilles, Jean-Philippe; Blanc, Raphael; et al.
Abstract : Background and Purpose: To assess the association between systolic blood pressure change (ΔSBP) at different time intervals after successful reperfusion with radiographic and clinical outcomes. Methods: This is a post hoc analysis of the BP-TARGET multicenter trial (Blood Pressure Target in Acute Stroke to Reduce Hemorrhage After Endovascular Therapy). ΔSBP was defined as end of procedure SBP minus mean SBP at different time intervals (15–60 minutes, 1–6 hours, and 6–24 hours postprocedure). The primary outcome was the poor functional outcome (90-day modified Rankin Scale score 3–6). Results: We included a total of 267 patients (130 in the intensive treatment group). Compared with patients with favorable outcome, patients with poor outcome had lower ΔSBP (less SBP reduction) at all times intervals. After adjusting for potential confounders including baseline SBP, both ΔSBP15 –60M and ΔSBP6 –24H were associated with lower odds of poor outcome (adjusted odds ratio per 5 mm Hg SBP reduction, 0.89 [95% CI, 0.81–0.99], and adjusted odds ratio 0.82 [95% CI, 0.73–0.92], respectively). Concerning safety outcomes, patients with intraparenchymal hemorrhage had lower ΔSBP at all time intervals. ΔSBP15 –60M was associated with lower odds of any intraparenchymal hemorrhage (adjusted odds ratio per 5 mm Hg SBP reduction 0.91 [95% CI, 0.83–0.99]). Conversely, ΔSBP was not associated with mortality or neurological deterioration at any time interval. Conclusions: After successful reperfusion, ΔSBP had a linear relationship with poor outcome and the risk of poor outcome was higher with less reduction from the baseline SBP. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03160677. Abstract : Supplemental Digital Content is available in the text.